Pengaruh Leverage dan Sales Growth Terhadap Financial Distress dengan Profitabilitas Sebagai Moderasi - Meita Dilani Nurhandriani; Nor Norisanti; R. Deni Muhammad Danial (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The transportation sector in Indonesia is one of the important sectors supporting the national economy. This sector consists of a variety of companies and has great potential for development. This research is based on the problem of decreasing demand due to restrictions on mobility and economic activity due to the pandemic. Causing a decrease in revenue and profits for transportation companies which can increase the risk of financial distress. This research uses financial leverage ratio calculations with DER (Debt Equity Ratio) and Sales growth to determine the effect on financial distress calculated using ICR and the role of profitability with ROA (Return On Assets) as moderation. The method used in this research is descriptive methods with a quantitative approach. Research on the transportation sector listed on the BEI in 2022. The research population was 49 companies with a sample of 41 companies. The financial distress method used is to calculate the ICR ratio (Interest Coverage Ratio) which is symbolized by a dummy. Data analysis uses multiple linear analysis and Moderating Regression Analysis (MRA) with the SPSS 26 application. Based on the research and discussion that has been carried out, the research results can be concluded that leverage has an effect but is not significant on financial distress. Sales growth has an effect but is not significant on financial distress. Profitability is able to moderate the relationship between leverage and financial distress and sales growth with financial distress.